An intervention targeting social, communication and daily activity skills in children and adolescents with Down syndrome and autism: a pilot study - Wester Oxelgren U (Dove Medical Press, 2019)
Ulrika Wester Oxelgren,1 Joakim Westerlund,2,3 Åsa Myrelid,1 Göran Annerén,4 Lotta Johansson,5 Marie Åberg,5 Jan Gustafsson,1 Elisabeth Fernell31Department of Women’s and Children’s Health, Uppsala University, Uppsala, Sweden; 2Department of Psychology, Stockholm University, Stockholm, Sweden; 3Gillberg Neuropsychiatry Centre, Department of Neuroscience and Physiology, Gothenburg University, Gothenburg, Sweden; 4Department of Immunology, Genetics, and Pathology, Science for Life Laboratory, Uppsala University, Uppsala, Sweden; 5Department of Health and Rehabilitation, Uppsala County, Kungsgärdet Center, Uppsala, SwedenPurpose: To evaluate whether an intervention, targeting deficits in social communication, interaction and restricted activities in children and adolescents with Down syndrome and autism could lead to enhanced participation in family and school activities.Methods: The intervention included education for parents and school staff about autism, and workshops to identify social-communication and daily living activities that would be meaningful for the child to practice at home and at school. Thereafter, a three-month period of training for the child followed. Outcome measures comprised evaluation of goal achievement for each child, the “Family Strain Index” questionnaire and a visual scale pertaining to the parents’ general opinion about the intervention.Results: On average, more than 90% of the goals were (to some extent or completely) achieved at home and at school. The mean scores of the “Family Strain Index” were almost identical at the follow-up to those before intervention. The evaluation supported that the use of strategies, intended to facilitate activities and communication, remained largely 18 months after start of the intervention.Conclusion: Despite the group involved in this study being composed of older children and adolescents, most of whom had severe and profound intellectual disability, the goal achievements and parents’ views on the intervention were encouraging.Keywords: Down syndrome, intellectual disability, autism, psychoeducational intervention